Guglielmo Marconi in Florence - Mazzinghi, Piero; Pelosi, Giuseppe (Il Colle di Galileo, 2019)
This brief note traces the interaction of Guglielmo Marconi, Nobel Prize winner for Physics in 1909, with the city of Florence through a selection of documents and pictures.